2009
DOI: 10.3144/expresspolymlett.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination of poly(dimethylsiloxane) surfaces by low pressure CF4 plasma – physicochemical and antifouling properties

Abstract: Abstract. Fluorinated surface groups were introduced into poly(dimethylsiloxane) (PDMS) coatings by plasma treatment using a low pressure radio frequency discharge operated with tetrafluoromethane. Substrates were placed in a remote position downstream the discharge. Discharge power and treatment time were tuned to alter the chemical composition of the plasma treated PDMS surface. The physicochemical properties and stability of the fluorine containing PDMS were characterized by X-ray photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 44 publications
5
33
0
Order By: Relevance
“…Different parameters can affect the plasma treatment process including treatment time, gas flow, gas pressure, and RF power. However, it is reported that treatment time is the most influential parameter among others . For this purpose, PECVD was applied and contact angle measurement was conducted to investigate its effects on the skin layer of membranes after the modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different parameters can affect the plasma treatment process including treatment time, gas flow, gas pressure, and RF power. However, it is reported that treatment time is the most influential parameter among others . For this purpose, PECVD was applied and contact angle measurement was conducted to investigate its effects on the skin layer of membranes after the modification.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is reported that treatment time is the most influential parameter among others. 30,41 For this purpose, PECVD was applied and contact angle measurement was conducted to investigate its effects on the skin layer of membranes after the modification. PECVD is a chemical vapor deposition process used to deposit thin films from a gas state (vapor) to a solid state on a substrate.…”
Section: Effect Of Fluorination Modificationmentioning
confidence: 99%
“…From this illustration, it can be concluded that it is relatively easy to assess or screen the performance of coatings for bacterial inhibition or release properties when compared to a reference. In addition, the assay was also briefly referred and illustrated for the assessment of other coating types [1,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one of its major components is fluorine (39.63%). The effect of fluorine on the inhibition of initial bacterial attachment was recently investigated [14]. The attachment of both hydrophilic and hydrophobic bacterial strains was dramatically reduced when introducing fluorine into a polydimethylsiloxane coating [14].…”
Section: Surface Elemental Compositionmentioning
confidence: 99%